Intelligence, creativity and gender as predictors of academic achievement among undergraduate students. - Naderi, Habibollah; Abdullah, Rohani; Tengku Abdul Hamid, Tengku Aizan; Sharir, Jamaluddin; Kumar, V. (Marsland Press, 2009)
The purpose of this cross – sectional study was to assess prediction of intelligence, creativity and gender on academic achievement among undergraduate students. Participants (N= 153, 105 = male & 48= female) completed intelligence and creativity tests which were compared with their cumulative grade point average (CGPA). A multiple regression analysis indicated that intelligence, creativity and gender explained 0.045 of the variance in academic achievement, which is not significant, as indicated by the F- value of 2.334. Multiple regression analyses also indicated that intelligence and creativity (gender is controlled) together explained 0.010 of the variance in academic achievement, which is also not significant, as indicated by the F- value of 1.562. Partial correlations between academic achievement and IQ, creativity scores and gender were non significant at .05. Coefficients also showed there is no significance between academic achievement and IQ and gender at .05, except for creativity (t= 2.008, p= 0.046). Finding shows predicting lower independent variables of this study (scores of intelligence, creativity and gender) on academic achievement (CGPA).